Improvements in Symptoms Following Neuronavigated Repetitive Transcranial Magnetic Stimulation (rTMS) in Severe and Enduring Anorexia Nervosa: Findings from two Case Studies. (24th October 2013) - McClelland, Jessica; Bozhilova, Natali; Nestler, Steffen; Campbell, Iain C.; Jacob, Shirabdi; Johnson‐Sabine, Eric; Schmidt, Ulrike
Abstract: Background: Advances in the treatment of anorexia nervosa (AN) are most likely to arise from targeted, brain‐directed treatments, such as repetitive transcranial magnetic stimulation (rTMS). We describe findings from two individuals with treatment‐resistant AN who received 19–20 sessions of neuronavigated, high frequency rTMS, applied to the left dorsolateral prefrontal cortex. Method: Within‐session measures assessed changes pre‐rTMS, post‐rTMS in subjective eating disorder (ED) experiences. Weight, ED symptoms and mood were assessed pre‐treatment, post‐treatment and at 1 month follow‐up. Results: In both cases, there was improvement in ED symptomatology and mood after 19–20 sessions of neuronavigated rTMS, and these changes persisted or continued to improve at follow‐up. Within sessions, Patient A demonstrated a consistent reduction in subjective ED experiences, and Patient B a reduction in some ED related experiences. Conclusions: These findings suggest that rTMS has potential as an adjunct to the treatment of AN and deserves further study. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.